2011
DOI: 10.1037/a0023509
|View full text |Cite
|
Sign up to set email alerts
|

Priming of reach and grasp actions by handled objects.

Abstract: Pictures of handled objects such as a beer mug or frying pan are shown to prime speeded reach and grasp actions that are compatible with the object. To determine whether the evocation of motor affordances implied by this result is driven merely by the physical orientation of the object's handle as opposed to higher-level properties of the object, including its function, prime objects were presented either in an upright orientation or rotated 90°from upright. Rotated objects successfully primed hand actions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 67 publications
4
85
1
Order By: Relevance
“…Viewing tools can modulate reaction times to initiate subsequent actions known as behavioral priming. Critically, these effects have been shown to reflect access to information about predicted tool-specific action outcomes according to previous knowledge of their common use (Masson et al, 2011). These findings coincide nicely with our interpretation of the current results.…”
Section: Affordance Specification For Toolssupporting
confidence: 90%
See 1 more Smart Citation
“…Viewing tools can modulate reaction times to initiate subsequent actions known as behavioral priming. Critically, these effects have been shown to reflect access to information about predicted tool-specific action outcomes according to previous knowledge of their common use (Masson et al, 2011). These findings coincide nicely with our interpretation of the current results.…”
Section: Affordance Specification For Toolssupporting
confidence: 90%
“…Simply viewing pictures of tools was found to activate left parietofrontal areas putatively important for actual tool use (Chao and Martin, 2000;Valyear et al, 2007) and to affect response times to initiate real actions according to affordances defined by both structural and functional tool properties (Bub et al, 2003;Bub et al, 2008). More recently, it was shown that affordance specification for tools includes information about predicted outcomes of actions in accordance with their conventional use (Masson et al, 2011), and reaction times to pantomime tool use with tools in hand are facilitated when preceded by passive viewing of real tools . These findings support the hypothesis that affordance specification in humans includes access to learned functional properties of objects based on previous experience.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, measuring three-dimensional movement trajectories, Till et al (2014) have reported that a visually presented manipu lable objects affect the online trajectories of reaching and grasping, biasing them in ways that are compatible with the presented object. Unlike the paradigms using button presses, these types of results do provide support for the notion the visual presentation of a manipulable object invokes sensorimotor simulations (see also Masson et al, 2011). While measuring specific grasp apertures and movement trajectories has promise for supporting more nuanced predictions of EC, and while these measures a not likely explained by spatial attentional biases, they still suffer from many of the criticisms of other research in EC.…”
Section: Behavioral Paradigmsmentioning
confidence: 65%
“…This type of result is consistent with a body of research that suggests a direct coupling between object perception and action. In a more specific demonstration of the coupling between object perception and action, Masson, Bub, and Breuer (2011) showed that manual actions toward objects are facilitated by the presentation of visual objects whose handles are orientated congruently with the targets. For example, visually presenting a picture of a beer mug with its handle oriented vertically facilitated vertical grasps to a grasping apparatus.…”
Section: Behavioral Paradigmsmentioning
confidence: 99%
“…Additionally, damage to regions of this network leads to ideomotor apraxia, characterized by disrupted tool usage but spared recognition (Haaland et al 2000;Johnson-Frey 2004). Finally, behavioral evidence suggests that simply viewing pictures of objects invokes motor representations of actions that those object afford (Grezes et al 2003;Humphreys et al 2004;Masson et al 2011;Tucker and Ellis 1998).…”
mentioning
confidence: 99%